2009
DOI: 10.1152/ajpheart.00368.2009
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces mitochondrial biogenesis in endothelial cells

Abstract: Pathways that regulate mitochondrial biogenesis are potential therapeutic targets for the amelioration of endothelial dysfunction and vascular disease. Resveratrol was shown to impact mitochondrial function in skeletal muscle and the liver, but its role in mitochondrial biogenesis in endothelial cells remains poorly defined. The present study determined whether resveratrol induces mitochondrial biogenesis in cultured human coronary arterial endothelial cells (CAECs). In CAECs resveratrol increased mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
302
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(323 citation statements)
references
References 49 publications
15
302
3
3
Order By: Relevance
“…The benefits of resveratrol for memory and prevention of neurodegenerative diseases is well documented in laboratory animals [74][75][76], and this aspect is only beginning to be explored through a number of ongoing human clinical trials ( Table 2 in Supporting Information). Resveratrol has been demonstrated to modulate mitochondrial biogenesis through activating PGC-1a [77,78], which may ultimately slow the aging process and prevent a number of chronic diseases [79] and improve muscular endurance [80]. Laboratory models have found resveratrol reduces oxidative stress in skeletal muscle following exercise [81] and disuse [82], and suppresses aging-associated decrements in physical performance [83], but does not attenuate sarcopenia [84].…”
Section: Current Limitations To Human Clinical Trial Datamentioning
confidence: 99%
“…The benefits of resveratrol for memory and prevention of neurodegenerative diseases is well documented in laboratory animals [74][75][76], and this aspect is only beginning to be explored through a number of ongoing human clinical trials ( Table 2 in Supporting Information). Resveratrol has been demonstrated to modulate mitochondrial biogenesis through activating PGC-1a [77,78], which may ultimately slow the aging process and prevent a number of chronic diseases [79] and improve muscular endurance [80]. Laboratory models have found resveratrol reduces oxidative stress in skeletal muscle following exercise [81] and disuse [82], and suppresses aging-associated decrements in physical performance [83], but does not attenuate sarcopenia [84].…”
Section: Current Limitations To Human Clinical Trial Datamentioning
confidence: 99%
“…Numerous studies in the literature also reported resveratrol protected cells from mitochondrial dysfunction [45][46][47]. Interestingly, resveratrol was found to increase the number of mitochondria in various cell lines and tissues, such as in Neuro2a cells [28], endothelial cells [56] and muscle [45]. In cultured human coronary arterial endothelial cells, resveratrol up-regulated protein expression of electron transport chain components, enhanced mitochondrial DNA content and mitochondrial mass, activated mitochondrial biogenesis factors (peroxisome proliferator-activated receptor- coactivator-1α PGC-1α, nuclear respiratory factor-1 NRF-1, mitochondrial transcription factor-A mtTF-A) [56].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human coronary arterial endothelial cells, resveratrol up-regulated protein expression of electron transport chain components, enhanced mitochondrial DNA content and mitochondrial mass, activated mitochondrial biogenesis factors (peroxisome proliferator-activated receptor- coactivator-1α PGC-1α, nuclear respiratory factor-1 NRF-1, mitochondrial transcription factor-A mtTF-A) [56]. Knockdown of NAD + -dependent protein deacetylase SIRT1 prevented resveratroltriggered mitochondrial biogenesis, suggesting that resveratrol elevated mitochondrial content in a SIRT1-dependent manner [56].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a polyphenolic antioxidant found in red wine, activating SIRT1 (Villalba and Alcain 2012;Wallerath et al 2002) prevents oxidative stress and coronary VSMC proliferation inhibiting extracellular signal regulated kinase (ERK) activation (Chong et al 2012;El-Mowafy et al 2008). Recent biophysical data indicate that resveratrol interacts with and modulates SIRT1 activity via an allosteric mechanism (Cencioni et al 2015;Hubbard et al 2013;Sinclair and Guarente 2014); these findings interestingly indicate that micromolar levels of resveratrol are sufficient to exert vasculoprotective effects through SIRT1 action (Csiszar et al 2009;Della-Morte et al 2009;Pacholec et al 2010;Ungvari et al 2007;Yang et al 2013). However, some data have suggested that resveratrol seems more likely act through a complex indirect mechanism dependent on the inhibition of phosphodiesterases (PDE) paralleled by AMPK activation (Beher et al 2009;Cencioni et al 2015;Park et al 2012;Yang et al 2013).…”
Section: The Sirtuin Familymentioning
confidence: 99%